P5005Diagnostic and prognostic utilities of insulin-like growth factor-binding protein-7 in patients presenting to the emergency department with dyspnea: results from the ICON-RELOADED study - Ibrahim, N; Chen-Tournoux, A; Christenson, R H; Gaggin, H K; Hollander, J E; Levy, P D; Mang, A; Masson, S; Nagurney, J T; Nowak, R; Pang, P S; Peacock, W F; et al. (European heart journal, 2019)
Abstract Background Increased activity of insulin-like growth factor–binding protein-7 (IGFBP7) is associated with cellular senescence, tissue aging, and obesity. Prior studies in chronic heart failure (HF) have linked IGFBP7 to impaired myocardial relaxation. The role of IGFBP7 measurement in acute HF remains unclear. Purpose To examine whether concentrations of IGFBP7 in patients presenting with dyspnea to the emergency department (ED) will aid in the diagnosis and prognosis of acute HF beyond N-terminal pro- B type natriuretic peptide (NT-proBNP). Methods The ICON-RELOADED (International Collaborative of NT-proBNP- Re-evaluation of Acute Diagnostic Cut-Offs in the Emergency Department) study was a prospective, multicenter clinical trial conducted at 19 sites in North America that enrolled subjects ≥22 years of age presenting to ED with complaints of dyspnea. Subjects were blindly adjudicated for the diagnosis of acute HF. A blood sample was taken at enrollment. Six-month prognosis for death/repeat hospitalization was obtained. IGFBP7 was measured using a pre-clinical research use only assay. Results Among 1449 patients (n=274 with acute HF), those with IGFBP7 concentrations in the highest quartile (>123.7 ng/mL) were older, more likely to be male and to have a history of hypertension and HF (all p<0.001). They also had lower estimated glomerular filtration rate (eGFR) and the lowest left ventricular ejection fraction (41% ± 21%) prior to study enrollment (all p<0.001). Independent predictors of IGFBP7 included age, male sex, history of diabetes, history of HF, and eGFR (all p<0.001). Median concentrations of NT-proBNP (2844 vs. 99 ng/mL) and IGFBP7 (146.1 vs. 86.1 ng/mL) were significantly higher in those with acute HF (both p<0.001); addition of IGFBP7 to NT-proBNP concentrations improved discrimination, increasing the area under the receiver operating curve for diagnosis of acute HF (from 0.91 to 0.94; p<0.001) (Figure 1). Addition of IGFBP7 to a complete model of independent predictors of acute HF (including NT-proBNP) improved model calibration; IGFBP7 also significantly re-classified acute HF diagnosis beyond NT-proBNP alone (net reclassification improvement +0.25; p<0.001). Higher log2-IGFBP7 concentrations predicted death/rehospitalization at 6 months (hazard ratio 1.74 per log2-standard deviation, 95% confidence interval 1.26–2.40, p=0.001). In Kaplan-Meier analyses, supramedian concentrations of IGFBP7 were associated with shorter event-free survival (log-rank p<0.001). ROC curve for diagnosis of acute HF Conclusions Among patients with acute dyspnea, concentrations of IGFBP7 add to NT-proBNP for diagnosis of acute HF and provide added prognostic utility for short-term risk. Acknowledgement/Funding Funding for this study was provided by Roche Diagnostics (Risch-Rotkreuz, Switzerland).